Biomechanical analysis of arm movement on shooting accuracy in petanque game - Supriaddin, Supriaddin; Satriawan, Rabwan; Nasrullah, Nasrullah; Shandi, Shutan Arie; Firdaus, Firdaus (Universitas Tanjungpura, 2026)
Background. The low and inconsistent shooting accuracy of petanque athletes in Bima Regency indicates that the application of biomechanical principles in arm movement techniques has not been optimal. This condition underscores the importance of conducting research to identify biomechanical factors as a scientific basis for improving athlete performance. Objective. This study aims to analyze the biomechanical components of arm movements which include backswing angle, release angle, swing speed, release speed, and joint coordination (shoulders, elbows and wrists) on shooting accuracy in petanque games. Method. This research uses quantitative methodsnon-experimental. The research subjects were 10 active petanque athletes, each of whom performed10 shooting attemptsdistance 7 meters.The research instrument used video recordings combined with the Kinovea application version 0.8.15. Data were analyzed using descriptive statistics, normality tests, Pearson correlation tests, and simple linear regression using SPSS 26. Results. The results of the statistical analysis show that the most effective backswing angle is at 70-88, realization angle 102-110, swing speed 1.40-1.60 m/s and realize speed 7.29-9.30 m/s. The results of the normality test showed that the data were normally distributed with a Sig >0.05. The Pearson correlation test showed that all variables were related to shooting accuracy.with the highest correlation value in joint coordination (r = 0.828; p = 0.003). Simple linear regression analysis shows that all variables have an effect on shooting accuracy where joint coordination is the highest with a value (r² = 0.686). The novelty of the research results shows that joint coordination is the most influential factor compared to other variables, so that these findings can be the basis for developing a biomechanics-based shooting training model and more effective and precise motor control. Conclusion. The conclusion of this study shows that the biomechanical variables of arm movement have a positive and significant effect on petanque shooting accuracy, with joint coordination being the primary factor in improving shooting precision. The findings provide a scientific contribution by identifying dominant biomechanical factors, as well as a practical contribution as a basis for developing more effective and targeted biomechanics-based training programs.